The effect of disability perception on the temporal distribution of emotionally charged autobiographical memories - Sofuoğlu, Gamze. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
One of the most common methods to investigate the relationship between autobiographical remembering and the self is to examine life span distribution of such memories. Numerous studies have observed an increase in the number of memories from one’s youth when identity formation is said to occur. Studies have shown that significant external events result in development of a new identity; this identity creates a change in temporal distribution of ABMs. In the present study; temporal distribution, narrative and phenomenological qualities of ABMs were investigated by taking disability perception and period of disability identity formation into consideration. Both visually disabled (VD) and sighted participants were asked to recall most important, happiest and saddest memories from their lives. Disabled participants also completed some additional questions about their disability perceptions. The results have demonstrated that VD and sighted show similar memory distributions for their most important and saddest memories. However, for happiest memories, VD group recalled events from predominantly the age between 20-29; whereas sighteds remembered events from the age 30-39. When the age of disability identity formation was used as starting point of memory distribution, the most important memories of VD participants primarily came from the first decade after the disability identity formation. Additionally, most of the happiest memories were related to the concept of achievement for VD participants; for sighted participants a similar relationship was observed in relationship related memories. Finally, VD participants mostly gave lower visual imagery ratings and higher auditory imagery and belief ratings for each type of memories.
Keywords: Autobiographical memory.; People with disabilities -- Functional assessment.; Disability evaluation.